Ultra-Narrow SPP Generation from Ag Grating - Gerald Stocker; Jasmin Spettel; Thang Duy Dao; Andreas Tortschanoff; Reyhaneh Jannesari; Gerald Pühringer; Parviz Saeidi; Florian Dubois; Clement Fleury; Cristina Consani; Thomas Grille; Elmar Aschauer; et al. (Sensors, 2021)
In this study, we investigate the potential of one-dimensional plasmonic grating structures to serve as a platform for, e.g., sensitive refractive index sensing. This is achieved by comparing numerical simulations to experimental results with respect to the excitation of surface plasmon polaritons (SPPs) in the mid-infrared region. The samples, silver-coated poly-silicon gratings, cover different grating depths in the range of 50 nm–375 nm. This variation of the depth, at a fixed grating geometry, allows the active tuning of the bandwidth of the SPP resonance according to the requirements of particular applications. The experimental setup employs a tunable quantum cascade laser (QCL) and allows the retrieval of angle-resolved experimental wavelength spectra to characterize the wavelength and angle dependence of the SPP resonance of the specular reflectance. The experimental results are in good agreement with the simulations. As a tendency, shallower gratings reveal narrower SPP resonances in reflection. In particular, we report on 2.9 nm full width at half maximum (FWHM) at a wavelength of 4.12 µm and a signal attenuation of <semantics>21%</semantics>. According to a numerical investigation with respect to a change of the refractive index of the dielectric above the grating structure, a spectral shift of <semantics>4122<mspace width="0.166667em"></mspace>nmRIU</semantics> can be expected, which translates to a figure of merit (FOM) of about 1421 <semantics>RIU−1</semantics>. The fabrication of the suggested structures is performed on eight-inch silicon substrates, entirely accomplished within an industrial fabrication environment using standard microfabrication processes. This in turn represents a decisive step towards plasmonic sensor technologies suitable for semiconductor mass-production.